Diagnosis, Preoperative Evaluation, and Assessment of Resectability of Pancreatic and Periampullary Cancer - Verma, Ashish (Indian J Surg, 2015)
Periampullary region encircles a radius of 2 cm around the ampulla of Vater; accordingly, four distinct neoplasias with overlapping imaging features originate in the region. Each of these lesions has a different long-term prognosis; hence, imaging evaluation to characterize the lesion is important. Further certain specific features pertaining to the vascular invasion and systemic spread may decide about the treatment as well as surgical approach. An understanding of the advances in imaging and image processing technology as well as in the methods of image acquisition, for the purpose, is quite relevant towards etching out a rational pre-treatment evaluation protocol. Further, an evidence-based decision as to the choice of optimum modality for answering specific clinical question is of prime importance in achieving a reasonable post-treatment outcome. Pancreatic adenocarcinoma is the fourth most common cancer and a malignancy with one of the least 5-year survival rates (ranging from 6.8 to 15 % depending on peripancreatic extensions, dropping to 1.8 % for metastatic disease). A survival rate of 15–27 % can be achieved if the lesion is resectable but unfortunately, only 10–15 % of patients are eligible for resection. Cystic tumors of pancreas are a rarer variety of pancreatic neoplasia (5–15 % of pancreatic cysts and 1 % of all pancreatic cancers) which have a much better outcome and chances of resection. Being mostly incidentalomas, a timely differentiation of this lesion from the much more common pseudocyst (which would mandate a medical management and a different surgical protocol) is the key for curability. Lastly, the neuroendocrine tumors of pancreas are equally rare (1 % of all pancreatic tumors), but importantly due to associated clinical syndromes and their capability to metastasize early in the course of disease, a timely detection may hence be the key for successful treatment of these lesions. Imaging plays a vital role in the initial detection and characterization as well as in determination of resectability of each of these pancreatic neoplasias. Further, the differentiation of pancreatic head tumors from other periampullary neoplasias is important; the fact that most recurrences are as a result of surgical intervention in an otherwise inoperable disease while most treatment failures are due to improper characterization of the lesion is notable.